Mobilising for women's rights and the role of resources : synthesis report, Bangladesh - Nazneen, Sohela; Sultan, Maheen; Mukhopadhyay, Maitrayee (Pathways of Women’s Empowerment and BRAC University, 2011)
Sohela Nazneen